Kajian Gender dalam Perspektif Agama Katolik di Kabupaten Sikka - Yohanes Fernando Banik; Gisela Nuwa; Petrus Kpalet (International Forum of Researchers and Lecturers, 2025)
This study aims to determine gender studies in the perspective of Catholicism in Sikka Regency and the challenges of gender justice in the perspective of Catholicism in Sikka Regency. This research was conducted using a qualitative descriptive approach. Data sources used are primary data sources and secondary data sources. The informants involved in this research are the parish priest of St Mary Immaculate Asumptha Habi, the Church Council and community leaders. Data Collection Techniques used are Observation, Interview, and Documentation Techniques. Data analysis techniques include data collection, data reduction, conclusion drawing and verification. The research results obtained are gender studies in the perspective of Catholicism in Sikka Regency and the challenges of gender justice in the perspective of Catholicism in Sikka Regency.